Composition for stripping agent, stripping method
Patent Information
- Application Number
- CN202611297464.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-25
- Publication Date
- 2026-10-16
AI Technical Summary
[0004]现有退镀工艺多采用高温长时间浸泡条件,通常操作温度不低于50℃,处理时间不少于5分钟,能耗较高,而且为了保证在高温下的剥离效率,现有的退镀剂往往含有较强腐蚀性的酸碱或氧化剂,不仅作用于保护膜,还可能对玻璃表面本身造成轻微腐蚀,导致玻璃表面粗糙度增加、透光率下降或产生蚀坑,严重影响后续镀膜或组装工序的质量
[0009]本发明提供的退镀剂用组合物中含有特定的第一保护剂(氮桥联多烷氧基硅烷)和第二保护剂(烷醇胺硼酸酯),二者复配后,通过界面化学键合、分子级协同交联与界面选择性吸附三重机制,在玻璃表面原位形成致密、高结合力的三维互穿网络防护层,既能够有效阻隔强酸对玻璃基底的侵蚀,实现玻璃表面粗糙度无劣化的低损伤退镀,又不会在金属镀层表面形成稳定吸附,保障退镀反应的正常进行,解决了玻璃表面金属镀层酸性退镀工艺中退镀效率与玻璃基底防护难以兼顾的行业共性技术难题。
Smart Images

Figure CN122916459A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of plating stripping technology, specifically to a composition for stripping agents and a stripping method. Background Technology
[0002] With the rapid development of the glass industry, the requirements for surface treatment processes of glass substrates are becoming increasingly stringent. In many precision glass processing procedures (such as etching, coating, laser cutting, and hot bending), in order to prevent the glass surface from being damaged or contaminated by heat in non-target areas, it is usually necessary to pre-coat a protective film on the glass surface. This protective film plays a crucial role in shielding and protecting the glass during subsequent high-temperature processing.
[0003] However, after the above processing steps are completed, the protective film needs to be completely removed from the glass surface to restore the cleanliness of the glass surface. This process is called "decoration" or "film removal".
[0004] Existing stripping processes often employ high-temperature, long-term immersion conditions, typically operating at temperatures no lower than 50°C and processing times no less than 5 minutes. This results in high energy consumption. Furthermore, to ensure efficient stripping at high temperatures, existing stripping agents often contain highly corrosive acids, alkalis, or oxidants. These not only affect the protective film but may also cause slight corrosion to the glass surface itself, leading to increased surface roughness, decreased light transmittance, or the formation of pits. This severely impacts the quality of subsequent coating or assembly processes.
[0005] In summary, there is an urgent need for a composition for a stripping agent that can effectively remove the coating while causing minimal damage to the glass substrate, without affecting optical performance, and effectively improving product yield. Summary of the Invention
[0006] The purpose of this invention is to provide a composition for stripping agents that can efficiently remove the film layer on the surface of glass substrates while reducing damage to the glass substrates; and does not affect the optical properties of the glass, resulting in a high product yield.
[0007] To achieve the above objectives, a first aspect of the present invention provides a composition for stripping plating, the composition comprising a stripping component and a glass protection component; the glass protection component comprising a first protectant and a second protectant; the first protectant being a nitrogen-bridged polyalkoxysilane; and the second protectant being an alkanolamine borate ester.
[0008] A second aspect of the present invention provides a method for stripping plating, the method comprising: stripping glass to be stripped in the presence of a stripping agent; The stripping agent includes the stripping agent composition described in the first aspect above.
[0009] The stripping agent composition provided by this invention contains a specific first protective agent (nitrogen-bridged polyalkoxysilane) and a second protective agent (alkanolamine borate). After the two are combined, a dense, highly bonded three-dimensional interpenetrating network protective layer is formed in situ on the glass surface through a triple mechanism of interfacial chemical bonding, molecular-level synergistic crosslinking, and interfacial selective adsorption. This effectively blocks the erosion of the glass substrate by strong acid, achieving low-damage stripping without deterioration of the glass surface roughness. At the same time, it does not form stable adsorption on the surface of the metal coating, ensuring the normal progress of the stripping reaction. This solves the common technical problem in the industry of the difficulty in balancing stripping efficiency and glass substrate protection in acidic stripping processes of metal coatings on glass surfaces.
[0010] The stripping method provided by this invention uses the stripping agent composition of this invention, which can achieve film stripping while achieving low damage to the glass substrate. Specifically, it has good surface roughness (Sa / Sz / Sq), no corrosion pits, no scratches, and almost no loss of light transmittance and flatness. It can basically meet the process requirement of "no polishing" after stripping, and provides a new technical path for cost reduction and efficiency improvement in the processing of high value-added glass products. Attached Figure Description
[0011] Figure 1 This is a SEM image of the product after plating removal in Embodiment 1 of the present invention; Figure 2 This is a SEM image of the product after plating removal in Embodiment 2 of the present invention; Figure 3 This is a SEM image of the product after plating removal in Embodiment 3 of the present invention; Figure 4 This is a SEM image of the product after plating removal in Example 4 of the present invention; Figure 5 This is a SEM image of the product after plating removal in Embodiment 5 of the present invention; Figure 6 This is a SEM image of the product after plating removal in Embodiment 6 of the present invention; Figure 7 This is a SEM image of the product after plating removal in Comparative Example 1 of the present invention; Figure 8 This is a SEM image of the product after plating removal in Comparative Example 2 of the present invention; Figure 9 This is a SEM image of the product after plating removal in Comparative Example 3 of the present invention; Figure 10 This is a SEM image of the product after deplating in Comparative Example 4 of the present invention. Detailed Implementation
[0012] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0013] In this invention, unless otherwise stated, the terms "first," "second," and the serial numbers "I," "II," etc., in the names of materials and operations do not represent a sequential order, nor do they limit the specific materials or operations. They are merely used to distinguish between different materials or operations. For example, "dispersion I," "dispersion II," etc., are only used to distinguish that these are not the same dispersion; "first mixture," "second mixture," etc., are only used to distinguish that these are not the same mixing operation. The definitions of the serial numbers in the remaining material names and operation names are similar and will not be elaborated upon here.
[0014] As previously described, a first aspect of the present invention provides a composition for stripping plating, the composition comprising a stripping component and a glass protection component; the glass protection component comprising a first protectant and a second protectant; the first protectant being a nitrogen-bridged polyalkoxysilane; and the second protectant being an alkanolamine borate ester.
[0015] The plating stripping agent composition provided by the present invention uses nitrogen-bridged polyalkoxysilane as the first protective agent and alkanolamine borate as the second protective agent, which are compounded to construct a protective system.
[0016] Research has revealed that, firstly, in this protective system, the first protective agent, when applied under acidic conditions, causes the alkoxysilanes at both ends of the nitrogen-bridged polyalkoxysilane molecule to hydrolyze into active silanol groups (-Si-OH). One of these silanol groups undergoes a dehydration condensation reaction with the silanol groups on the glass surface, forming Si-O-Si covalent bonds. This enables the film layer to achieve a chemical bond-level bond with the glass substrate, ensuring that the protective layer is not easily desorbed during stripping cycles. The other silanol group undergoes intermolecular lateral condensation crosslinking with adjacent silane molecules, forming a continuous, highly crosslinked rigid network polymer skeleton. This physically blocks the penetration channels of the stripping components, effectively overcoming the shortcomings of monofunctional silane films, such as loose film formation and susceptibility to pinhole defects.
[0017] Secondly, the second protective agent in this protective system, alkanolamine borate, has a small molecular structure that can penetrate into the microscopic voids, pinhole defects, and grain boundary micro-defects of the film formed by the first protective agent. It can perform point repair on weak points of physical barriers, complementing the planar coverage of the first protective agent and eliminating potential channels for corrosion by stripping components. After penetrating the defects, the BOC bond of the second protective agent can further react with the residual silanol (-Si-OH) of the first protective agent or the silanol (Si-OH) on the glass surface to form BO-Si bridging bonds, connecting the film to the substrate and the voids inside the film into a more complete network. Its rigid structure provides stronger mechanical support after filling. At the same time, the second protective agent has a stable structure of intramolecular N→B coordination bonds, with a controllable hydrolysis rate. The N→B bonds can be opened / closed to achieve a "repair-stabilization" cycle. Furthermore, the hydroxyl (-OH) and amino (-NH-) groups of the alkanolamine in the second protective agent are strongly polar groups that can form strong hydrogen bonds with the silanol hydroxyl (Si-OH) groups on the glass surface. Through hydrogen bonds, the agent is firmly adsorbed onto the glass or the surface of the first protective layer, maintaining the position of the repair agent at the defect and preventing it from being washed away. More importantly, the boron atom in the alkanolamine borate ester molecule has an electron-deficient structure and Lewis acidity, which can form a B←N coordinate bond with the nitrogen atom of the amino group in the first protective agent. This allows the second protective agent molecule to be chemically anchored in the silane polymer network, improving the overall crosslinking density and structural stability of the protective layer.
[0018] According to a preferred embodiment, the nitrogen-bridged polyalkoxysilane provides the nitrogen bridging with an amino group and / or a urea group, preferably an amino group. In this case, the bridging organic amino group in the molecular structure of the first protective agent has a dual function: firstly, the amino nitrogen atom has Lewis basicity and can serve as a coordination active site, providing an anchoring site for the chemical bonding of the second protective agent; secondly, when applied in an acidic environment, the amino group can undergo protonation, forming a local buffer microenvironment at the film interface, slowing down the diffusion of hydrogen ions into the film interior and the glass surface, and further improving the acid resistance of the film.
[0019] Preferably, the composition contains 1.7-3.2 wt% of the glass protective component based on the total mass of the composition.
[0020] According to a preferred embodiment, in the composition for stripping the plating, the mass ratio of the first protective agent to the second protective agent is 1:(1.5-3.5), more preferably 1:(2.2-2.8). Studies have found that this preferred embodiment provides the best glass protection effect.
[0021] In a preferred embodiment, the first protective agent is selected from at least one of bis[3-(trimethoxysilyl)propyl]amine, bis[3-(triethoxysilyl)propyl]amine, N,N'-bis(3-trimethoxysilylpropyl)ethylenediamine, and 1,3-bis(trimethoxysilylpropyl)urea.
[0022] Preferably, the second protective agent is selected from at least one of triethanolamine borate, triisopropanolamine borate, diethanolamine borate, and monoethanolamine borate.
[0023] In the preferred case described above, the first and second protective agents form a stable intermolecular synergistic system after being compounded: the rigid framework of the first protective agent can physically shield the second protective agent from direct attack by the acidic environment, effectively inhibiting its acid decomposition and extending the service life of the second protective agent; while the boron-oxygen structure in the second protective agent forms a weak coordination interaction with the amino group in the first protective agent, which significantly inhibits the hydrolysis and desorption of the first protective agent under acidic conditions, and improves the adsorption strength and structural stability of the first protective agent.
[0024] In a preferred embodiment, based on the total mass of the composition, the stripping component comprises 57.0-60.9 wt% acidic substance, 15.2-17.0 wt% oxidant, 2.9-3.5 wt% passivating agent, 14.7-16.5 wt% chelating agent, and 2.6-4.7 wt% penetrant. In this preferred embodiment, it exhibits excellent stripping effect on PVD coatings including alumina, titanium, and copper on glass; the glass protectant can achieve better synergy with the stripping component, jointly maintaining the stripping system to effectively and quickly remove the glass film while minimizing damage to the glass substrate, thus achieving a balance between protective performance and stripping efficiency.
[0025] In some preferred embodiments, the acidic substance includes organic acids and / or aminosulfonic acids, and the oxidant is persulfate. In this preferred case, the acidic substance is relatively mild, enabling gentle chemical etching of the oxide coating; the persulfate rapidly releases active oxygen in this acidic system, causing breakdown and loosening of the coating and reverse oxidation, disrupting the dense structure of the coating, and causing internal cracks and peeling of the film, achieving rapid physical removal and laying the foundation for subsequent chemical reactions.
[0026] In some preferred embodiments, the passivating agent is a water-soluble chloride. Addressing the problem that the dense TiO2 passivation oxide film easily forms on the surface of metallic titanium, hindering etching by the etching solution, the water-soluble chloride in the formulation dissociates into chloride ions in the acidic stripping system. These chloride ions preferentially adsorb onto grain boundaries or defects on the coating surface, inducing localized pitting corrosion and preventing the formation of the passivation film, thereby activating the titanium substrate to promote rapid and continuous dissolution of the titanium layer; simultaneously, the reacted Ti... 4+ It exists stably in solution under the action of chelating agents, preventing Ti from4+ Hydrolysis produces a mist-like precipitate that contaminates the surface of the microcrystalline glass. This "pitting effect" works synergistically with the "oxidative loosening" of persulfate, transforming the originally dense oxide layer into a porous, sponge-like structure. This greatly increases the contact area between the acid and the underlying metal, significantly accelerating the chemical dissolution rate of the metal coating.
[0027] According to another preferred embodiment, the chelating agent comprises at least chelating agent I, chelating agent II, and chelating agent III in a mass ratio of (12.0-17.6):(8.3-14.0):1; chelating agent I is a chelating agent containing phosphonic acid groups, chelating agent II is a chelating agent containing hydroxyl and carboxyl groups, and chelating agent III is a chelating agent containing phosphate groups. In this preferred embodiment, chelating agent I, chelating agent II, and chelating agent III form a multi-component synergistic chelating system for the stripped and dissolved Cu. 2 + Ti 4+ Al 3+ Plasma performs rapid, efficient, and high-capacity complexation, preventing metal ions from redepositing on the glass surface or forming flocculent precipitates, ensuring the continuous and efficient stripping reaction, and ultimately achieving complete removal of the coating without residue.
[0028] In some embodiments, the chelating agent I is selected from at least one of 2-phosphonobutane-1,2,4-tricarboxylic acid, hydroxyethylidene diphosphonic acid, and aminotrimethylene phosphonic acid.
[0029] In some embodiments, the chelating agent II is selected from at least one of gluconate, tartrate, and citrate.
[0030] In some embodiments, the chelating agent III is selected from at least one of phytate, pyrophosphate, and tripolyphosphate.
[0031] In some specific embodiments, the persulfate is selected from at least one of (NH4)2S2O8, Na2S2O8, and 2KHSO5•KHSO4•K2SO4.
[0032] In a preferred embodiment, the passivating agent is selected from at least one of sodium chloride, potassium chloride, and ammonium chloride.
[0033] In a preferred embodiment, the penetrant is selected from at least one of isohexyl glycol, dipropylene glycol methyl ether, and propylene glycol methyl ether. This preferred penetrant possesses excellent penetrating and wetting properties, accelerating the stripping reaction rate at room temperature; furthermore, it also has defoaming and solubilizing effects, effectively ensuring system stability.
[0034] Preferably, the organic acid includes sulfonic acid organic acids and hydroxycarboxylic acid organic acids; based on the total mass of the composition, the composition includes 41.4~45.0 wt% of the sulfonic acid organic acid and 15.6~15.9 wt% of the hydroxycarboxylic acid organic acid. In this preferred embodiment, a stable acidic environment can be continuously provided, which has strong penetrating power, effectively reducing the adhesion between the coating and the glass interface, avoiding substrate damage caused by violent reactions, and achieving controllable stripping at room temperature.
[0035] In some specific embodiments, the sulfonic acid is methanesulfonic acid; the hydroxycarboxylic acid is selected from at least one of glycolic acid, malic acid, and citric acid. These acids are relatively mild and can more effectively reduce the risk of damage to the glass substrate during the stripping reaction.
[0036] In some specific embodiments, the gluconate is sodium gluconate or potassium gluconate.
[0037] In some specific embodiments, the tartrate is sodium tartrate or potassium tartrate.
[0038] In some specific embodiments, the citrate is sodium citrate or potassium citrate.
[0039] In some specific embodiments, the phytate is sodium phytate or potassium phytate.
[0040] In some specific embodiments, the pyrophosphate is sodium pyrophosphate or potassium pyrophosphate.
[0041] In some specific embodiments, the tripolyphosphate is sodium tripolyphosphate or potassium tripolyphosphate.
[0042] The present invention provides an exemplary method for preparing a plating stripping agent used in a specific embodiment: the plating stripping agent is mixed with the components in the composition and water by stirring to obtain the plating stripping agent.
[0043] In some embodiments, the amount of water used is 130-165 parts by weight relative to 100 parts by weight of the plating stripping agent composition.
[0044] As mentioned above, a second aspect of the present invention provides a method for stripping plating, the method comprising: stripping glass to be stripped in the presence of a stripping agent; The stripping agent includes the stripping agent composition described in the first aspect above.
[0045] In some embodiments, the glass to be decoated is 3D microcrystalline glass.
[0046] According to one specific embodiment, the method further includes: subjecting the stripped material to alkaline washing.
[0047] In a preferred embodiment, the conditions for the stripping process include: a temperature of 25-30°C and a time of 1-2 minutes.
[0048] Preferably, the alkaline washing conditions include a temperature of 90-100℃ and a time of 1-3 minutes. Under this preferred condition, the micro-stress generated on the glass surface due to coating and decoating is released, and surface defects such as micro-unevenness, scratches, and grain boundary protrusions soften and smooth in situ under alkaline atmosphere, thereby reducing surface roughness.
[0049] In a preferred embodiment, the alkaline reagent used in the alkaline washing process contains 80-120 g / L potassium hydroxide and / or sodium hydroxide, 70-90 g / L gluconate, 20-40 g / L metasilicate pentahydrate, 40-60 g / L tetraacetate diglutamate, and 40-60 g / L monoethanolamine. The strongly alkaline environment (pH > 13) constructed by potassium hydroxide and sodium hydroxide efficiently hydrolyzes and removes the silane coupling agent-based protective film remaining from the previous acidic process, exposing a clean glass active surface. The complexation system composed of gluconate and tetraacetate diglutamate can chelate and remove trace metal ions remaining on the glass surface, adsorb impurities, purify surface active sites, and provide a guarantee for surface performance recovery. The pentahydrate metasilicate reacts with monoethanolamine at high temperature to form an ultra-thin, dense, and transparent silicate repair layer in situ on the glass surface. This repair layer can fill micro-pits, smooth surface micro-undulations, effectively reduce surface roughness, and improve surface optical uniformity. By leveling the microstructure and cleaning surface impurities, the surface roughness (Sa) and optical transmittance of the repaired microcrystalline glass can be restored to the level before coating, fully meeting the requirements for use as an optical-grade cover for 3D glass smartphone displays.
[0050] In some embodiments, the tetrasodium glutamate diacetate is tetrasodium glutamate diacetate or tetrapotassium glutamate diacetate.
[0051] In some embodiments, the pentahydrate metasilicate is sodium metasilicate pentahydrate or potassium metasilicate pentahydrate.
[0052] In some embodiments, the method further includes: after the alkaline washing, acid washing with 4-6 wt% citric acid. Citric acid can quickly and gently neutralize residual alkaline reagents on the glass surface, preventing the alkaline components from remaining for a long time and causing the glass to whiten. In addition, it can chelate and remove trace amounts of adsorbed silicate ions and metal impurities on the surface, ensuring surface cleanliness. Subsequent rinsing with pure water ensures that the glass surface ultimately reaches a neutral, clean, watermark-free, and residue-free optical-grade state, providing a clean base for subsequent use.
[0053] Unless otherwise specified, room temperature refers to a temperature of 25-30℃.
[0054] The present invention will be described in detail below through examples. Unless otherwise specified, the instruments, reagents, and materials involved in the following examples are all conventional instruments, reagents, and materials, which can be obtained through legitimate commercial channels. Unless otherwise stated, all reagents used are commercially available analytical grade products.
[0055] Oxidizing agent: Ammonium persulfate has the chemical formula (NH4)2S2O8.
[0056] The potassium persulfate complex salt has the chemical formula 2KHSO5•KHSO4•K2SO4.
[0057] First protective agent: Bis[3-(trimethoxysilyl)propyl]amine, abbreviated as BTMSPA.
[0058] Bis[3-(triethoxysilyl)propyl]amine, abbreviated as BTESPA.
[0059] N,N'-Bis(3-trimethoxysilylpropyl)ethylenediamine, abbreviated as BTMSPEDA.
[0060] 3-Aminopropyltriethoxysilane, abbreviated as KH-550.
[0061] Second protective agent: Triethanolamine borate, abbreviated as TEA-B.
[0062] Triisopropanolamine borate, abbreviated as TIPA-B.
[0063] Diethanolamine borate, abbreviated as DEA-B.
[0064] Chelating agent I: 2-Phosphosphonobutane-1,2,4-tricarboxylic acid, abbreviated as PBTCA.
[0065] Hydroxyethylidene diphosphonic acid, abbreviated as HEDP.
[0066] Aminotrimethylenephosphonic acid, abbreviated as ATMP.
[0067] Alkaline reagent: Alkaline aqueous solution, wherein the concentration of potassium hydroxide is 100 g / L, the concentration of sodium gluconate is 80 g / L, the concentration of sodium metasilicate pentahydrate is 30 g / L, the concentration of tetrasodium diacetate of glutamic acid is 50 g / L, and the concentration of monoethanolamine is 50 g / L.
[0068] Example 1 According to the formulation of the stripping agent composition in Table 1, the components of the stripping agent composition and water (the total mass of the stripping agent composition is 100 parts by weight, and the amount of water is 145.6 parts by weight) are first stirred and mixed to obtain the stripping agent; and the 3D microcrystalline glass film layer (copper-titanium aluminum oxide coating) is stripped according to the following steps: S1. First, load the glass to be decoated onto the platform and conveyor to adapt to the continuous production line; S2. In the presence of the stripping agent, the glass to be stripped is subjected to stripping treatment (pump circulation, 25°C, 1 min); then it is rinsed in water tank 1 (pure water, bubbling, 50°C, 2 min, to initially remove residual acidic stripping agent from the surface). S3. The material from step S2 is subjected to alkaline washing with an alkaline reagent (pump circulation, 95±3℃, 2min); then it is passed through water washing tank 2 (pure water, bubbling, 50℃, 2min). S4. The material from step S3 is pickled with 5wt% citric acid (bubbling, 50℃, 2min); then it is sequentially passed through washing tank 3 (pure water, bubbling, 50℃, 2min), washing tank 4 (pure water, bubbling, 50℃, 2min), washing tank 5 (pure water, bubbling, 55℃, 2min), and drying tank (80℃, 2min) to obtain a clean, texture-free, non-concave polishing 3D microcrystalline glass product, which is then conveyed to the platform for unloading.
[0069] Unless otherwise specified, Examples 2-6 and Comparative Examples 1-4 were carried out using methods similar to those in Example 1, except for the formulation of the composition for the stripping agent, as shown in Table 1; all other parts not listed are the same as in Example 1. In Table 1, aminosulfonic acid and sulfonic acid organic acids are collectively referred to as sulfonic acids.
[0070] Table 1
[0071] Continued from Table 1
[0072] Note: The mass content of each component in the table refers to the percentage of the pure substance in the total mass of the composition for stripping agent.
[0073] The mass ratio 1 refers to the ratio of the first chelating agent: the second chelating agent: the third chelating agent.
[0074] The mass ratio 2 refers to the ratio of the first protective agent to the second protective agent.
[0075] " / " indicates that it does not contain.
[0076] Test case The performance of the glass after stripping of the aforementioned embodiments and comparative examples was tested, as follows: 1. Roughness was tested according to the ISO 25178 standard method (three samples were randomly selected, and three points were randomly selected from each sample, resulting in three tests, and the average value was obtained. Sa is the arithmetic mean height, which characterizes the overall undulation level of the glass surface. Within the measurement area, it is the average of the absolute values of the deviations of the height of each sampling point from the average plane height; Sz is the maximum height, which characterizes the extreme undulation range of the surface. Within the measurement area, it is the vertical distance between the highest peak and the lowest valley; Sq is the root mean square height, which characterizes the microscopic fineness and smoothness of the surface. Within the measurement area, the average value of the squared height deviations of each profile is calculated, and then the square root is taken). 2. Test transmittance according to the ISO 15368:2021 standard method (take 3 sheets at random, and test 3 points at random on each sheet for a total of 3 tests, and take the average value). 3. Test the haze according to the ASTM D1003-21 standard method (take 3 samples at random, and take 3 points at random on each sample for a total of 3 tests and take the average value). 4. The stability of the stripping agent was tested according to the comprehensive evaluation method for the stability of chemical reagents in GB / T 23945-2023. The test conditions were uniform: room temperature 25℃, dynamic pump circulation, and stripping operation time of 1 min. 5. Test the defoaming ability of the stripping agent using the dynamic cycling method specified in GB / T 21885-2023; The test results are shown in Table 2: Table 2
[0077] Continued from Table 2
[0078] Note: Acceptable thresholds: Sa≤1nm, Sz≤50nm, Sq≤5nm, transmittance≥91%, haze≤0.4%; Corrosion grade classification standard: Grade 0: No corrosion → No surface fogging, no pitting, no grain boundary deterioration, and complete microstructure; Level 1: Slight micro-corrosion → Only grain boundary micro-corrosion and micro-pitting corrosion, no obvious haze visible to the naked eye, and slightly excessive optical indicators; Level 2: Slight surface corrosion → slight haze visible to the naked eye, localized fine haze, roughness / haze significantly exceeds the standard; Level 3: Moderate to significant corrosion → large-area fogging, grain boundary corrosion, and deterioration of surface texture; Level 4: Severe corrosion → obvious pitting, discoloration, fogging, and damage to the glass substrate.
[0079] Metal coating residue level determination criteria: Level 5 Extremely Severe Residue: Large areas of metal plating remain, with very poor overall removal; the board surface is covered with patches of unremoved plating. Level 4 Severe Residue: Uneven removal of coating, with obvious coating residue visible in multiple locations throughout the entire area, and incomplete overall removal of coating; Level 3 Moderate Residue: Plating remains in localized areas, with prominent residue at corners / gaps, and the main panel surface is basically clean. Level 2 Slight Residue: Only scattered dots and small patches of coating residue remain, accounting for a small proportion and having little visual impact; Level 1 Trace Residue: Only extremely fine traces of plating remain, barely visible to the naked eye, almost completely removed; Grade 0 - No Residue: The metal plating is completely removed, leaving no trace of plating on the board surface; the plating removal is thorough.
[0080] Defoaming ability rating standards: Superior: The dynamic pump circulation process generates no foam, and any small amount of foam can be eliminated instantly, keeping the liquid surface clean for a long time without any foam interfering with the production process. Good: The operation process generates only a small amount of foam, the foam dissipates quickly, there is no foam accumulation throughout the process, and it does not affect the wetting of the workpiece and normal production; Generally: A small amount of floating bubbles are continuously generated under pump circulation conditions. The foam dissipates slowly and the defoaming margin is insufficient, which can only meet the needs of short-term simple processing. Poor: The system produces a large amount of foam, which accumulates continuously and is difficult to eliminate, exceeding the defoaming capacity of the liquid itself and seriously interfering with pump circulation and process operation.
[0081] Stability rating standards for pharmaceutical solutions: Excellent: The liquid phase of the drug solution is clear and uniform, without layering, precipitation, turbidity or colloidal aggregation; the continuous pump circulation operation has stable performance without fluctuation, the components have good compatibility, and there is no activity decay after long-term use. Good: The overall liquid phase state of the solution is stable and there are no abnormalities; the dynamic operating conditions are stable, the stripping and corrosion inhibition effects are not significantly fluctuating, and only a small amount of synergistic components are missing, which does not affect the basic performance of the system. Generally: There are deviations in the acid-base balance, chelation effect or corrosion inhibition ratio of the system; silane hydrolysis micro-agglomeration is prone to occur, and the performance of the process may fluctuate slightly, but there is no problem of chemical deterioration and failure. Poor: The solution is prone to turbidity and gel floc precipitation; the composition is severely unbalanced, the activity of the solution is greatly reduced, and it cannot meet the requirements of normal process use.
[0082] 6. The microstructure of the products after plating removal in Examples 1-6 and Comparative Examples 1-4 was tested using electron microscopy. The results are as follows: Figures 1-10 As shown: Figures 1-6 The images shown are SEM images of the products after plating removal in Examples 1 to 6. Figures 7-10 SEM images of the products after plating removal for Comparative Examples 1 to 4.
[0083] The results above demonstrate that the plating stripping agent composition provided by this invention has the following significant advantages compared to the prior art (comparative example): (1) After processing in all embodiments (1-6) of the present invention, the surface roughness (Sa≤0.98nm, Sz≤49.6nm, Sq≤4.98nm) and optical performance (transmittance≥90.9%, haze≤0.4%) of the workpiece strictly meet the preset high-precision qualification thresholds, and the concave surfaces can all achieve "polishing-free" processing. In contrast, the surface roughness (Sa>1.04nm, Sz>51.3nm) and optical performance (transmittance0.42%) of all comparative examples (1-4) exceed the standards, and all require additional "heavy polishing" or "light polishing" processes to meet the basic requirements. This fully demonstrates that the composition formulation for stripping agent provided by the present invention can effectively replace the traditional polishing process, significantly shorten the production process, and reduce labor and equipment costs.
[0084] (2) All embodiments of the present invention achieved "Level 0 corrosion-free" during the stripping process, indicating that the protective components in the formulation can work synergistically to form perfect passivation protection on the substrate while removing the film. In contrast, Comparative Examples 1-3 all showed "Level 2 mild corrosion", and Comparative Example 4 also showed "Level 1 micro-corrosion", indicating that the existing technology cannot effectively inhibit the corrosion reaction, which can easily lead to a decrease in product yield or even scrap. The present invention fundamentally solves the problem of substrate damage during the stripping process, improving the reliability and consistency of the product.
[0085] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.
Claims
1. A composition for stripping plating, characterized in that, The composition contains a stripping component and a glass protection component; the glass protection component includes a first protectant and a second protectant; the first protectant is a nitrogen-bridged polyalkoxysilane; the second protectant is an alkanolamine borate.
2. The composition for stripping plating according to claim 1, characterized in that, Based on the total mass of the composition, the composition contains 1.7-3.2 wt% of the glass protective component; And / or, the nitrogen-bridged polyalkoxysilane is provided by an amino group and / or a urea group; And / or, in the composition for stripping, the mass ratio of the first protective agent to the second protective agent is 1:(1.5-3.5).
3. The composition for stripping plating according to claim 2, characterized in that, The first protective agent is selected from at least one of bis[3-(trimethoxysilyl)propyl]amine, bis[3-(triethoxysilyl)propyl]amine, N,N'-bis(3-trimethoxysilylpropyl)ethylenediamine, and 1,3-bis(trimethoxysilylpropyl)urea; And / or, the second protective agent is selected from at least one of triethanolamine borate, triisopropanolamine borate, diethanolamine borate, and monoethanolamine borate.
4. The composition for stripping plating according to any one of claims 1-3, characterized in that, Based on the total mass of the composition, the stripping component comprises 57.0-60.9 wt% acidic substance, 15.2-17.0 wt% oxidant, 2.9-3.5 wt% passivating agent, 14.7-16.5 wt% chelating agent and 2.6-4.7 wt% penetrant.
5. The composition for stripping plating according to claim 4, characterized in that, The acidic substance includes organic acids and / or aminosulfonic acids, and the oxidizing agent is persulfate; And / or, the passivating agent is a water-soluble chloride.
6. The composition for stripping plating according to claim 4, characterized in that, The chelating agent comprises at least chelating agent I, chelating agent II, and chelating agent III in a mass ratio of (12.0-17.6):(8.3-14.0):1; chelating agent I is a chelating agent containing phosphonic acid groups, chelating agent II is a chelating agent containing hydroxyl and carboxyl groups, and chelating agent III is a chelating agent containing phosphate groups.
7. The composition for stripping plating according to claim 6, characterized in that, The chelating agent I is selected from at least one of 2-phosphonobutane-1,2,4-tricarboxylic acid, hydroxyethylidene diphosphonic acid, and aminotrimethylene phosphonic acid; And / or, the chelating agent II is selected from at least one of gluconate, tartrate, and citrate; And / or, the chelating agent III is selected from at least one of phytate, pyrophosphate, and tripolyphosphate.
8. The composition for stripping plating according to claim 5, characterized in that, The persulfate is selected from at least one of (NH4)2S2O8, Na2S2O8, and 2KHSO5•KHSO4•K2SO4; And / or, the passivating agent is selected from at least one of sodium chloride, potassium chloride, and ammonium chloride; And / or, the penetrant is selected from at least one of isohexyl glycol, dipropylene glycol methyl ether, and propylene glycol methyl ether; And / or, the organic acid includes sulfonic acid organic acids and hydroxycarboxylic acid organic acids; based on the total mass of the composition, the composition includes 41.4 to 45.0 wt% of the sulfonic acid organic acid and 15.6 to 15.9 wt% of the hydroxycarboxylic acid organic acid; Preferably, the sulfonic acid is methanesulfonic acid; the hydroxycarboxylic acid is selected from at least one of glycolic acid, malic acid, and citric acid.
9. A method for stripping plating, characterized in that, The method includes: performing a stripping treatment on the glass to be stripped in the presence of a stripping agent; The stripping agent comprises the stripping agent composition according to any one of claims 1-8.
10. The plating stripping method according to claim 9, characterized in that, The method further includes: subjecting the deplating treated material to alkaline washing; And / or, the conditions for the stripping process include: a temperature of 25-30°C and a time of 1-2 minutes; And / or, the alkaline washing conditions include: a temperature of 90-100℃ and a time of 1-3 min; And / or, the alkaline reagent used in the alkaline washing contains 80-120 g / L of potassium hydroxide and / or sodium hydroxide, 70-90 g / L of gluconate, 20-40 g / L of metasilicate pentahydrate, 40-60 g / L of tetraacetic acid diacetate, and 40-60 g / L of monoethanolamine.